Identification of Amino Acids Important for Substrate Specificity in Sucrose Transporters Using Gene Shuffling - Reinders, Anke (American Society for Biochemistry and Molecular Biology, 2012)
Plant sucrose transporters (SUTs) are H(+)-coupled uptake transporters. Type I and II (SUTs) are phylogenetically related but have different substrate specificities. Type I SUTs transport sucrose, maltose, and a wide range of natural and synthetic α- and β-glucosides. Type II SUTs are more selective for sucrose and maltose. Here, we investigated the structural basis for this difference in substrate specificity. We used a novel gene shuffling method called synthetic template shuffling to introduce 62 differentially conserved amino acid residues from type I SUTs into OsSUT1, a type II SUT from rice. The OsSUT1 variants were tested for their ability to transport the fluorescent coumarin β-glucoside esculin when expressed in yeast. Fluorescent yeast cells were selected using fluorescence-activated cell sorting (FACS). Substitution of five amino acids present in type I SUTs in OsSUT1 was found to be sufficient to confer esculin uptake activity. The changes clustered in two areas of the OsSUT1 protein: in the first loop and the top of TMS2 (T80L and A86K) and in TMS5 (S220A, S221A, and T224Y). The substrate specificity of this OsSUT1 variant was almost identical to that of type I SUTs. Corresponding changes in the sugarcane type II transporter ShSUT1 also changed substrate specificity, indicating that these residues contribute to substrate specificity in type II SUTs in general.